Performance Analysis of Openlitespeed and Apache Web Servers in Serving Client Requests - Sandra, Haris (Knowbase : International Journal of Knowledge in Database, 2022)
Web server those who use apache are now very familiar to users, because apache is easier to use than other web servers, but runs PHP applications (Hypertext Preprocessor) by handling 100000 requests is certainly very influential on the speed of the web server. Openlitespeed is a web server that functions the same as apache, but server users are more likely to use openlitespeed. This study conducted a performance test on both web servers to find out which web server is very suitable for use in completing client requests. This test uses the https://webpagetest.org, https://gtmetrix.com and https://developers.google.com/speed/pagespeed/insights applications. To do benchmarking of the many diverse client requests. The trial results in the current study provide benchmarking results which result in terms of time usage.